Performance Characteristics of Pine Oil Mixed Diesel Fueled Single Cylinder Four Stroke Diesel Engine - Joshi, Ishwar; Adhikari, Surya Prasad (Himalayan Journal of Applied Science and Engineering, 2021)
In this study, biodiesel from the stem of Pinus roxburghii was prepared by steam distillation process. Consequently, the physical and thermal properties of pine biodiesel (P100), and 20 % pine-biodiesel and 80 % diesel (P20) were tested on American Society for Testing and Materials (ASTM) standards. The test results confirmed that the thermophysical properties of pine biodiesel and its blend were suitable for the fuel in diesel engine without any modification in the test engine. Eventually, the engine performance and combustion parameters were evaluated for pine-biodiesel blend for 5 % biodiesel and 95 % diesel (P5), 10 % biodiesel and 90 % diesel (P10), 15 % biodiesel and 85 % diesel (P15) and P20, and compared with diesel on Kirloskar Single Cylinder Compression Ignition Engine for a compression ratio of 15:1. In the midst of those in different blends evaluated, P15 showed the better brake specific fuel consumption (BSFC) i.e 18.75 % lower than diesel fuel particularly up to 50 % of the engine load. However, at higher load, decrease rate in BSFC of P15 fuel is lower than engine load up to 50 %. Similarly, brake thermal efficiency (BTE) of P15 increases to 13.5% mainly on 50 % loading condition of the engine. At above, increment rate of BTE of pine oil biodiesel compared to diesel decreases. The brake power (BP) and brake mean effective pressure (BMEP) of P15 also found nearer to diesel. However, the BP of P15 found higher compared to diesel in all loading conditions. Thus, from the experimental investigations, P15 blend of pine oil biodiesel was found to be amenable for its use in compression ignition (CI) engine without any modification, as the BTE and SFC were found to better and, BP, indicated power (IP) and BMEP were also found nearer to diesel fuel.